Feeding the world well : a framework for ethical food systems - Goldberg, Alan M.; Wychgram, Cara, 1988- (Johns Hopkins University Press, 2020)
"This edited collection advances the discussion of ethical food production and the many elements that have to be balanced in order to achieve it. A large group of contributors from academia and industry prepare the food production industry for a world in which "ethical" or "sustainable" production practices are not only trendy but necessary to ensuring that we can feed the world's growing population"--